Eliminating electromechanical instability in dielectric elastomers by employing pre-stretch. (26th May 2016) - Jiang, Liang; Betts, Anthony; Kennedy, David; Jerrams, Stephen
Abstract: Electromechanical instability (EMI) is one of most common failure modes for dielectric elastomers (DEs). It has been reported that pre-stretching a DE sample can suppress EMI due to strain stiffening taking place for larger strains and a higher elastic modulus are achieved at high stretch ratios when a voltage is applied to the material. In this work, the influence of equi-biaxial stretch on DE secant modulus was studied using VHB 4910 and silicone rubber (SR) composites containing barium titanate (BaTiO3, BT) particles and also dopamine coated BT (DP-BT) particles. The investigation of equi-biaxial deformation and EMI failure for VHB 4910 was undertaken by introducing a voltage-stretch function. The results showed that EMI was suppressed by equi-biaxial pre-stretch for all the DEs fabricated and tested. The stiffening properties of the DE materials were also studied with respect to the secant modulus. Furthermore, a voltage-induced strain of above 200% was achieved for the polyacrylate film by applying a pre-stretch ratio of 2.0 without EMI occurring. However, a maximum voltage-induced strain in the polyacrylate film of 78% was obtained by the SR/20 wt% DP-BT composite for a lower applied pre-stretch ratio of 1.6 and again EMI was eliminated.